2008
DOI: 10.1590/s0103-84782008000400023
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between clinical and postmortem evaluation in repeat breeder beef cows

Abstract: The objective of this study was to investigate the causes of the repeat breeder syndrome comparing clinical signs and postmortem findings in beef cows. The identification of factors affecting the reproductive tract can support decisions as to whether treatment of repeat breeder cows is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Where possible, gynaecological evaluations in live animals should proceed with proper history, clinical and laboratory examination in order to determine specific aetiologies and generate useful data for effective diagnosis of genital disorders. This approach coupled with assessment of serum hormone profiles could hasten decisions for or against remedial measures to be deployed in the management of reproducti ve disturbances (Ferreira et al, 2008). For example, it has been suggested that under oestrogenic influence (follicular phase), the uterus is more resistant to bacterial invasion than during the prevalence of high progesterone (luteal phase) in animals (Adams, 1975;Amin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Where possible, gynaecological evaluations in live animals should proceed with proper history, clinical and laboratory examination in order to determine specific aetiologies and generate useful data for effective diagnosis of genital disorders. This approach coupled with assessment of serum hormone profiles could hasten decisions for or against remedial measures to be deployed in the management of reproducti ve disturbances (Ferreira et al, 2008). For example, it has been suggested that under oestrogenic influence (follicular phase), the uterus is more resistant to bacterial invasion than during the prevalence of high progesterone (luteal phase) in animals (Adams, 1975;Amin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The bull-cow interaction usually ranges from 45 to 90 days, although sometimes it lasts 6 months or it may also be permanent. Few reports on RBC exist in beef cattle (Maurer & Echternkamp, 1985;Ferreira et al, 2008).…”
Section: Importance Of Rbc In Beef Cattlementioning
confidence: 99%
“…The uterine adenomyosis was observed in heifers/cows culled at slaughterhouses by Monteiro et al (2003), who observed the occurrence of 26.7%, by Moreira et al (2006) founded 70%, and by Ferreira et al (2008) where were observed 53% of adenomyosis in repeat breeder beef cows. These percentages are conflicting; however the adenomyosis is not an unusual finding in cows, as reported in the classical literature (Jubb andKennedy 1987, McEntee 1990), and a scarcity of records of this dystrophy in cows may be justified to be a myometrial injury that does not make up endometrial biopsy samples.…”
Section: Introductionmentioning
confidence: 96%
“…Occurrences of reproductive disturbances in women (Devlieger and D'Hooghe 2003;Levgur et al 2000) and animals Mori et al 2001;Ferreira et al 2008;Moreira et al 2008) have been associated to adenomyosis.…”
Section: Introductionmentioning
confidence: 99%